Is ‘Priority’ Just? Rethinking Constitutional Fairness in Indonesia’s Mining Law - Abd. Rohman; Rizky Bangun Wibisono (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The governance of natural resources in Indonesia, especially the mining sector, remains a contested legal domain involving intersecting economic, political, and constitutional interests. Article 6 paragraph (1) letter j of Law No. 3/020 grants the central government the authority to designate WIUPK “on a priority basis,” raising constitutional questions about its alignment with Article 33 paragraph (3) of the UUD NRI 1945. Critics argue that the vague term “priority” invites discretionary abuse, perpetuates structural inequalities, and potentially legitimizes monopolistic practices in the name of development. This study aims to critically examine the constitutionality and practical implications of the said provision using a normative legal research approach. The method involves statutory analysis, jurisprudential review, and interpretative evaluation of relevant constitutional principles, including distributive justice and economic democracy. The findings suggest that while the provision may be justified as an affirmative policy instrument to promote equitable access to natural resources, its current formulation lacks clear legal criteria, thereby opening space for misuse. The Constitutional Court's Decision No. 77/PUU-XXII/2024 affirms that any prioritization must be grounded in transparent, accountable mechanisms and should reflect the principle of social justice. This decision also signals the importance of inclusive governance, public participation, and state responsibility in preventing legal inequality. Without substantial regulatory reform, the application of “priority” risks contradicting the very essence of constitutional fairness.